2005
DOI: 10.1007/s10163-005-0135-4
|View full text |Cite
|
Sign up to set email alerts
|

Recycling building demolition waste in hot-mix asphalt concrete: a case study in Kuwait

Abstract: Building demolition waste constitutes a major component of municipal solid waste in Kuwait. Over 90% of this waste is currently land-filled, causing extreme pressure on the available land-fill sites. At the same time, the sources of natural aggregates are almost depleted, and there is an increasing demand because of the increased construction and maintenance activities. This article presents the results of a technical feasibility study into meeting this need by recycling the aggregates obtained from building d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
20
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(28 citation statements)
references
References 5 publications
(5 reference statements)
3
20
0
2
Order By: Relevance
“…As seen in Table 2, several studies concluded that mixtures using RCA generally meet the national specifications for water resistance [38][39][40]48,51,52,54]. Many of these studies qualify this finding by stating that the resistance to the action of water decreases with an increasing percentage of RCA [40,48,51]; therefore, for percentages of RCA over 75%, the specifications are not met [45].…”
Section: Moisture Damage Resistancementioning
confidence: 79%
See 1 more Smart Citation
“…As seen in Table 2, several studies concluded that mixtures using RCA generally meet the national specifications for water resistance [38][39][40]48,51,52,54]. Many of these studies qualify this finding by stating that the resistance to the action of water decreases with an increasing percentage of RCA [40,48,51]; therefore, for percentages of RCA over 75%, the specifications are not met [45].…”
Section: Moisture Damage Resistancementioning
confidence: 79%
“…However, Pasandín and Pérez [44] reported that curing a mixture of RCA for 4 h in an oven did not significantly affect the Marshall stability. Despite the variety of reported results, a common key conclusion can be extracted from the literature review: the bituminous mixtures using RCA generally meet the national Marshall stability and flow specifications [28,[30][31][32][33]36,48,[51][52][53]. Therefore, these mixtures will have a sufficient capacity to withstand traffic loads.…”
Section: Marshall Flow and Marshall Stabilitymentioning
confidence: 98%
“…The hazardous wastes list is available as per the European Regulation [6][7][8][9]. Inert CDW can be processed and made suitable for use in road construction, e.g., [10][11][12][13][14]. Other research studies have clearly suggested the possibility of properly treating and reusing such waste as aggregate in new concrete (especially lower level applications) [15][16][17][18][19][20][21][22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…have been recycled and reused in some applications. Similarly, the reuse of recyclable materials has been under study for many years through technological work and research on the environmental impact of such practices [4][5][6][7][8][9]. The recycling of industrial waste in civil engineering applications has remarkable potential in the long term.…”
Section: Introductionmentioning
confidence: 99%